Responsabilidade penal institucional: um ensaio propositivo sobre a culpabilidade da pessoa jurídica - Simão, Fernando Geraldo (2025)
The central problem of this study is the inadequacy of traditional theories of culpability, which focus on individuals, for criminally holding legal entities accountable under criminal law. The increasing complexity of corporations and the lack of specific procedural rules create difficulties in applying effective criminal sanctions without violating fundamental principles, such as culpability and legal certainty. Large corporations, especially in globalized contexts, have been notably involved in contemporary crimes, causing significant social harm. Consequently, impunity or arbitrary punishment creates serious legal and social imbalances. This study proposes the theory of institutional culpability, a distinct subtype of traditional intent or negligence. By rejecting strict liability, the study argues that culpability must be assessed through systemic failures and deliberate institutional choices, requiring proof of an "institutional intent", expressed through internal policies, corporate governance, and structured decisions. Effective compliance mechanisms were considered important mitigating factors, whereas clear organizational failures could enable criminal liability without the need for dual imputation. The research identified a critical gap within the Brazilian legal system regarding normative coherence and procedural specificity necessary to adequately address institutional culpability. International examples, such as the models adopted in Spain, France, Chile, and Argentina, provided useful and inspiring perspectives for constructing a new Brazilian model. Particularly highlighted was Carlos Gómez-Jara Díez’s constructivist model of corporate culpability, which inspired new doctrinal proposals on the subject. These findings indicate that institutional culpability is a viable and necessary alternative for criminally holding legal entities accountable, strengthening the Rule of Law and preventing arbitrary decisions. The proposed thesis demonstrates that, without specific mechanisms and clearly defined processes, the application of criminal law to corporations will remain ineffective. Therefore, it urgently suggests developing new substantive and procedural rules capable of ensuring legal certainty, proportionality, and effectiveness in the Brazilian criminal justice system.